2019
DOI: 10.18805/ijar.b-842
|View full text |Cite
|
Sign up to set email alerts
|

Lactogenic effects of the leaf’s powder of Spondias mombin L. on West African Dwarf (WAD) sheep performance and serum prolactin level in Republic of Benin

Abstract: Twenty four (24) dairy ewes at the 4th stage of lactation were used to assess the milk production and serum prolactin level of ewes treated with leaf’s powder of Spondias mombin. The lactating ewes were selected and divided into 4 groups of 6 ewes per group: control group (no fed powder of Spondias mombin), Galactin group (no fed powder of Spondias mombin but treated with lactogenic drug) and groups treated with powder of Spondias mombin (group single dose and group double dose). The parameters measured includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…De même, malgré les efforts d'investissement dans la filière lait et viande, avec l'importation des bovins Girolando, les vaches de races locales ne produisent que 0,5 à 2 litres de lait en moyenne par jour et 4 à 7 L/j pour les races améliorées en station (métis Gir et Girolando) (Toukourou et Senou 2010), ce qui est considérablement inférieur aux standards internationaux. Les techniques classiques d'amélioration de la production et de la conservation du lait de vache et des produits laitiers sont onéreuses et peu accessibles aux éleveurs et aux transformateurs de l'Afrique et en particulier du Bénin (Akouedegni et al, 2013). Ainsi le recours aux espèces exotiques de caprins est un des moyens les plus sûrs pour booster la production de viande et de lait au Bénin (Offoumon et al, 2018 ;Vissoh et al, 2021).…”
Section: Introductionunclassified
“…De même, malgré les efforts d'investissement dans la filière lait et viande, avec l'importation des bovins Girolando, les vaches de races locales ne produisent que 0,5 à 2 litres de lait en moyenne par jour et 4 à 7 L/j pour les races améliorées en station (métis Gir et Girolando) (Toukourou et Senou 2010), ce qui est considérablement inférieur aux standards internationaux. Les techniques classiques d'amélioration de la production et de la conservation du lait de vache et des produits laitiers sont onéreuses et peu accessibles aux éleveurs et aux transformateurs de l'Afrique et en particulier du Bénin (Akouedegni et al, 2013). Ainsi le recours aux espèces exotiques de caprins est un des moyens les plus sûrs pour booster la production de viande et de lait au Bénin (Offoumon et al, 2018 ;Vissoh et al, 2021).…”
Section: Introductionunclassified
“…Results of alternative feeds on milk production show that Spondias mombin extract improves milk production in ewes (14) with an average of 100.63 g/day (Table 4). According to Pamo et al (15) who carried out studies on the chemical composition and effect of supplementation with Calliandra calothyrsus and Leucaena leucocephala on milk production in goats, fresh leaves of Calliandra calothyrsus and Leucaena leucocephala doubled production (361 g/d) in dairy goats.…”
Section: Effects Of Alternative Feeds Milk Production and Composition...mentioning
confidence: 99%
“…Studies on the effects of cassava and banana peels (12) showed that incorporating dried banana peels at 20% in the feed accelerated sheep growth and average daily weight gain. Moreover Kiéma et al (13) showed that the use of Faidherbia albida pods increase average daily weight gain of young bulls therefore seems to be an alternative way of improving livestock production (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies investigated S. mombin leaves impact on milk production for improvement of breeding in the West African Dwarf sheep. These investigations from Benin and Nigeria observed lactogenic effects of fresh or dried S. mombin leaves fed to ewes as an increase of the milk yield, the serum prolactin levels as wells as the lamb's body weight gains [10,11,32,33] . In the present study, the aqueous of S. mombin leaf extract inhibited the mammary differentiation of HC11 cells, as the β-casein mRNA expression was half of that induced in the DMSO-treated control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%